Diagenesis of Magnetic Minerals in Active/Relict Methane Seep: Constraints From Rock Magnetism and Mineralogical Records From Bay of Bengal - Gaikwad, Virsen; Badesab, Firoz; Dewangan, Pawan; Kotha, Mahender (Frontiers in Earth Science, 2021)
In this study, we conducted a comprehensive investigation of rock magnetic, mineralogical, and sedimentological records of sediment cores supplemented by a high resolution seismic data to elucidate the controls of structural and diagenetic (early vs. late) processes on the sediment magnetism in active and relict cold seep sites in the Bay of Bengal. Two distinct sediment magnetic zones (Z-I and Z-II) are defined based on the down-core variations in rock magnetic properties. The sediment magnetism is carried by complex magnetic mineral assemblages of detrital (titanomagnetite, titanohematite) and authigenic (fine-grained greigite) minerals. Overall, the magnetic susceptibility varies over one order of magnitude with highest values found in relict core. Uppermost sediment magnetic zone (Z-I) is characterized by higher concentration of magnetite as seen through elevated values of magnetic susceptibility (χlf) and saturation isothermal remanent magnetization (SIRM). A systematic gradual decrease of χlf and IRM1T in Z-I is attributed to the progressive diagenetic dissolution of iron oxides and subsequent precipitation of iron sulfides. Magnetic grain size diagnostic (ARM/IRM1T) parameter decreases initially due to the preferential dissolution of fine-grained magnetite in the sulfidic zone (Z-I), and increases later in response to the authigenic formation of magnetite and greigite in methanic zone (Z-II). Distinct low S-ratio and χlf values in methanic zone of relict core is due to increased relative contribution from highly preserved coercive magnetic (titanohematite) grains of detrital origin which survived in the diagenetic processes. A strong linkage between occurrence of authigenic carbonates and greigite formation is observed. Two plausible mechanisms are proposed to explain the formation and preservation of greigite in Z-I and Z-II: 1) decline in methane flux due to massive hydrate accumulation within the active fault system and formation of authigenic carbonate crust in the sub-surface sediments hindered the supply of upward migrating fluid/gas; thereby limiting the sulfide production which preferentially enhanced greigite formation in Z-I and 2) restricted supply of downward diffusing sulfide by the carbonate layers in the uppermost sediments created a sulfide deficient zone which inhibited the pyritization and favoured the formation of greigite in the methanic zone (Z-II).